ANALISIS KESULITAN BELAJAR BAGI SISWA DI MTS SEJAHTERA BERSAMA RAMBAH SAMO KEC. RAMBAH SAMO KAB. ROKAN HULU - -, Hardianto (Edu Research, 2015)
This research is motivated by the problems in MTs Sejahtera Bersama RambahSamo about the difficulties of students' learning. The purpose of this study was to know how the difficulties and obstacles encountered in the students' learning. This research is quantitative research. Population in this research is class VIII totaling 19 people. Data collected by observation, interviews and questionnaires. The data analysis was done by using a percentage. The study says that learning disabilities are at high category with a percentage of 83.79% adversity. Difficulty learning from factors within the students are also in a high category with a percentage of 84.74%. The difficulties of students' learning from external factors also are at high category with a percentage of 82.70%. While the perceived barriers for students to learn such a lack of desire to learn, lack of encouragement from family, school climate and the lack of social control. It is advisable for students to be able to identify their learning difficulties and find solutions to difficulties. Teachers are also expected to help students identify the difficulties of students' learning.